The Relationship between Organizational Intelligence and the Ability of Managers and Employees in University Libraries - Adel Soleimani Nejad,; Fariborz Doroudi; Tayebeh Khajeh (کتابداری و اطلاع‌رسانی, 2023)
Objective: Organizational intelligence is defined as the act of acquiring comprehensive knowledge and information about all the affecting factors on the organization. This very key factor capacitates managers and employees to make decisions on such factors affecting the organization in order to gain a competitive advantage. Employing Organizational solutions can raise the organization's competitive power and discriminate it from other organizations. Organizational intelligence can function as a supporting entity for other organizations and enables them to benefit from the competition while using valuable information. This study aims to investigate relationship between organizational intelligence and managerial ability of managers and employees of university libraries in Kerman.Methodology: This research is applied in terms of purpose and descriptive in terms of correlation type. To collect the data, a 37-item organizational intelligence questionnaire and a 31-item management capabilities questionnaire of managers and employees were used. Descriptive statistics were used to analyze the data. The convenience sample included managers and employees of university libraries in Kerman including central Library of Shahid Bahonar University, central Library of University of Medical Sciences, central Library of Islamic Azad University, and central Library of Payam- Noor University. The study included 32 participants so the census method was used due to its limited number and all the participants were studied. The validity and reliability of the questionnaires were obtained by face validity and Cronbach’s alpha test. The reliability of the questionnaire for organizational intelligence and managers’ and employees’ capabilities are 88 percent and 90 percent respectively.Findings: The findings of the study indicate a significant relationship between the capabilities of managers and employees of university libraries in Kerman and organizational intelligence. That is, with the rise and fall of organizational intelligence, those capabilities increased or decreased. Also, the findings show that there is a significant relationship between the managing capabilities of managers and organizational intelligence. In addition, it was found that there is a significant relationship between the behavioral capabilities of managers and employees of university libraries in Kerman, and organizational intelligence. It was also found that there is a significant relationship between the structural capabilities of managers and organizational intelligence.Conclusion: The findings revealed that from the managers and employees of these libraries’ viewpoints, management played a proper role in promoting their professional spirit. Taking the effective components into consideration in the planning, implementation and effectual feedback will significantly improve the activities of the libraries. The employees of the libraries have a favorable and propitious feeling towards their organization and have evaluated the workplace as having suitable conditions. They also have a relatively good feeling about their professional activities and carry out the shouldered responsibility appropriately. Also, the common fate, professional spirit, work solidarity, agreement, and the employment of knowledge had a somewhat effect on the structural capabilities of managers and on those libraries. Strategic plans in those organizations are somewhat comprehensible for managers and employees and for success, managers believe in the perspective of the organization with a sense of continued dependency on their organization, so they tend to make more attempts to achieve success.